Adaptasi Alat Ukur Intolerance of Uncertainty Scale-12 (IUS-12) - Fito Gusmantyo; Salma Putri Rahayu; Karina Nurrosmariza; Annisa Nabilah Prameswari Yuda Praja; Diah Zaleha Wyandini; Ghinaya Ummul Mukminin Hidayat (Humanitas (Jurnal Psikologi), 2025)
Anxiety is one of the topics that has attracted the attention of several parties recently, especially among students. The anxiety experienced by students when facing uncertainty at a reasonable level of intensity can be considered to have positive value, but if anxiety reaches a high level, it can cause negative effects. The purpose of this study is to adapt the Intolerance of Uncertainty Scale-12 (IUS-12) measurement tool into a version that is relevant for Indonesian students. This adaptation involves translation and cultural and linguistic adjustments, with a focus on two main dimensions: Prospective Intolerance of Uncertainty and Inhibitory Intolerance of Uncertainty. The study included 200 active students aged 18–23 years. Data collection was conducted using accidental sampling. The scale used in this measurement tool is a five-point Likert scale with 12 items. Data collection methods used questionnaires distributed online and offline. Data collection used a measurement tool to assess individuals' inability to cope with uncertainty, namely the Intolerance of Uncertainty Scale-12 (IUS-12). The psychometric analysis included item analysis, factor analysis using Confirmatory Factor Analysis (CFA), which included factor loading analysis, model fit testing, and reliability testing. The reliability result of this measurement tool was 0.795, which falls into the good category and indicates that this measurement tool is reliable for measuring the construct of intolerance to uncertainty among university students. However, the results of the item analysis and factor loading analysis were still unsatisfactory, as the factor loading values were > 0.4. Three items need to be eliminated based on the analysis results. Therefore, further research is needed to improve the quality of the measurement tool so that it can be used optimally, especially in the Indonesian cultural context. This study is expected to contribute to the development of psychological measurement tools that are more appropriate for the Indonesian cultural context.